2007
DOI: 10.1007/s00382-007-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of recent El Niño Modoki on dry/wet conditions in the Pacific rim during boreal summer

Abstract: Present work uses 1979-2005 monthly observational data to study the impacts of El Niño Modoki on dry/wet conditions in the Pacific rim during boreal summer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
335
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(379 citation statements)
references
References 73 publications
(79 reference statements)
35
335
1
8
Order By: Relevance
“…For the newer record, we can confirm that central Pacific events tend to start later in the calendar year than eastern-Pacific events (Kao and Yu, 2009), but found that most events of either type end up becoming basin-wide nevertheless, rendering their distinction less meaningful once fully established. In a related matter, we understand that so-called El Niño Modoki events (Weng et al, 2007(Weng et al, , 2009) are simplified versions of the 2nd principal component of the tropical Pacific SST field which by definition is orthogonal to the 1st principal component of this field (which, in turn, depicts the SST pattern associated with ENSO). However, since the Modoki SST pattern is frozen in space through the year (Weng et al, 2007), while the MEI (and MEI.ext) shows some seasonal variation of its loading patterns, it turns out that the MEI is not always orthogonal to Modoki SST.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…For the newer record, we can confirm that central Pacific events tend to start later in the calendar year than eastern-Pacific events (Kao and Yu, 2009), but found that most events of either type end up becoming basin-wide nevertheless, rendering their distinction less meaningful once fully established. In a related matter, we understand that so-called El Niño Modoki events (Weng et al, 2007(Weng et al, , 2009) are simplified versions of the 2nd principal component of the tropical Pacific SST field which by definition is orthogonal to the 1st principal component of this field (which, in turn, depicts the SST pattern associated with ENSO). However, since the Modoki SST pattern is frozen in space through the year (Weng et al, 2007), while the MEI (and MEI.ext) shows some seasonal variation of its loading patterns, it turns out that the MEI is not always orthogonal to Modoki SST.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In a related matter, we understand that so-called El Niño Modoki events (Weng et al, 2007(Weng et al, , 2009) are simplified versions of the 2nd principal component of the tropical Pacific SST field which by definition is orthogonal to the 1st principal component of this field (which, in turn, depicts the SST pattern associated with ENSO). However, since the Modoki SST pattern is frozen in space through the year (Weng et al, 2007), while the MEI (and MEI.ext) shows some seasonal variation of its loading patterns, it turns out that the MEI is not always orthogonal to Modoki SST. In fact, from April-May to June-July, the MEI.ext time series correlates with the Modoki time series around −0.35 between 1950 and 2005.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It is completely different from the conventional ENSO with warming (cooling) SST anomalies in the tropical eastern Pacific (i.e., eastern-Pacific (EP) ENSO) in both the spatial pattern and climate impacts (Feng et al 2010(Feng et al , 2011Weng et al 2007;Wang and Wang 2014;Yang and Jiang 2014;Yu and Kim 2011;Zhang et al 2013; among others). For example, Weng et al (2007Weng et al ( , 2009 gave us a general comparison of the impacts of CP and EP El Niño on the Pacific rim regions for the winter and summer seasons. Yuan et al (2012) suggested that evolutions of the anomalous Philippine Sea anticyclone that bridges El Niño to the East Asian climate display distinct features in the location, intensity and lifetime for the CP and EP ENSO through the linear partial correlation method.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to SIOD and SAM, tropical modes of variability such as El Niño-Southern Oscillation (ENSO) (both conventional and Modoki types) and IOD are also considered. The conventional ENSO and IOD indices are taken from Lestari and Koh (2016), whereas the ENSO Modoki index is taken from Weng et al (2007). They are defined in Eqs.…”
Section: Linear Regression Against Climate Indicesmentioning
confidence: 99%